2020
DOI: 10.7897/2277-4572.091160
|View full text |Cite
|
Sign up to set email alerts
|

Method Development, Validation by Simultaneous Estimation of Empagliflozin and Linagliptin by Rp-HPLC Method

Abstract: A very simple, accurate, precise, robust, rugged and stability indicating method with gradient elution was developed for simultaneous estimation of Empagliflozin and Linagliptin by RP-HPLC method. The chromatographic conditions were successfully developed for the separation of Empagliflozin and Linagliptin by using C18 (Equisil BDS) column (4.6 × 250 mm) 5μ, flow rate was 0.7 ml/min, mobile phase ratio was (40:60 v/v) methanol: water, detection wavelength was 224 nm and 294 nm. The instrument used was SHIMADZU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…LIG was investigated using spectrophotometric and chromatographic methods in pure form, in pharmaceutical dosage form, and in biological fluids (Mai et al, 2020;Nannapaneni et al, 2016). On the contrary, several analytical methods based on spectrophotometry (Abdel-Ghany et al, 2017;Moussa et al, 2018) and chromatography (Abdel-Ghany et al, 2016;Ayoub, 2015;Bhole et al, 2017;Dayyih et al, 2021;EL Sheikh et al, 2020;Naazneen & Sridevi, 2016;Raut et al, 2020;Rizk et al, 2021) were described for the simultaneous determination of LIG and EMG. In addition, several methods were reported for the simultaneous quantitation of LIG and MEF in pure form, in pharmaceutical dosage form, or in human plasma.…”
Section: Introductionmentioning
confidence: 99%
“…LIG was investigated using spectrophotometric and chromatographic methods in pure form, in pharmaceutical dosage form, and in biological fluids (Mai et al, 2020;Nannapaneni et al, 2016). On the contrary, several analytical methods based on spectrophotometry (Abdel-Ghany et al, 2017;Moussa et al, 2018) and chromatography (Abdel-Ghany et al, 2016;Ayoub, 2015;Bhole et al, 2017;Dayyih et al, 2021;EL Sheikh et al, 2020;Naazneen & Sridevi, 2016;Raut et al, 2020;Rizk et al, 2021) were described for the simultaneous determination of LIG and EMG. In addition, several methods were reported for the simultaneous quantitation of LIG and MEF in pure form, in pharmaceutical dosage form, or in human plasma.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature search revealed that several analytical methods were reported for the analysis of metformin HCl, linagliptin, empagliflozin, a combination of metformin and linagliptin, a combination of metformin and empagliflozin, and a combination of linagliptin and empagliflozin using Ultraviolet spectroscopy [13][14][15][16], reverse phase high-performance liquid chromatography (RP-HPLC) [17][18][19][20][21][22][23][24][25], and ultra-performance liquid chromatography (UPLC) [26,27]. However, only a few RP_HPLC methods were reported for the simultaneous determination of metformin HCl, linagliptin, and empagliflozin in their recently approved fixed dosage combinations [28][29][30] and thus, there is a need to develop rapid, sensitive, and cost-effective stability indicating RP-HPLC method for the simultaneous estimation of metformin HCl, linagliptin and empagliflozin in fixed dosage combinations.…”
Section: Fig 1: Chemical Structure Of Metformin Hclmentioning
confidence: 99%
“…15 Empaglif lozin can be estimated using limited highperformance liquid chromatography (HPLC), reverse-phase high-performance liquid chromatography (RP-HPLC), and ultraviolet (UV) methods, according to a survey of the relevant published research. [16][17][18][19][20][21][22][23][24][25][26][27][28] This study was undertaken to determine the best RP-HPLC technique aimed at determining the quantity of empagliflozin in both bulks and pharmaceutical dosage forms. The recommendations laid out by ICH were used to perform the technique validation.…”
Section: Introductionmentioning
confidence: 99%